1999
DOI: 10.1002/1529-0131(199911)42:11<2319::aid-anr9>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Significant loss of bone mass in patients with early, active ankylosing spondylitis: A followup study

Abstract: Objective. To analyze whether inflammatory disease activity plays a substantial role in the loss of bone mass observed in ankylosing spondylitis (AS) patients who have not yet developed ankylosis.Methods. A longitudinal cohort study of 34 patients with early AS (duration <10 years) without ankylosis was conducted. The mean followup was 19 months. Loss of bone mass in defined regions of the lumbar spine and femoral neck was analyzed by dual x-ray absorptiometry. Patients were grouped according to biologic param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
3
11

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(71 citation statements)
references
References 18 publications
5
52
3
11
Order By: Relevance
“…Similar to these findings, bone resorption markers have been found to be increased in AS, especially in patients with active disease (23,24), which most likely is a reflection of trabecular bone loss as the basis of osteoporosis and increased fracture risk in AS. MRI has been very helpful in clarifying the pathologic events in AS (4,(25)(26)(27).…”
Section: Transformation From Acute Inflammation To New Bone Formationsupporting
confidence: 68%
“…Similar to these findings, bone resorption markers have been found to be increased in AS, especially in patients with active disease (23,24), which most likely is a reflection of trabecular bone loss as the basis of osteoporosis and increased fracture risk in AS. MRI has been very helpful in clarifying the pathologic events in AS (4,(25)(26)(27).…”
Section: Transformation From Acute Inflammation To New Bone Formationsupporting
confidence: 68%
“…Even the patients with no movement restriction in the early stage of the disease might experience bone loss caused by inflammatory activity (22,23). In our study, BMD values of the patients in the PsA group were lower than controls; however, there was no significant relation between disease duration and BMD values.…”
Section: Discussioncontrasting
confidence: 60%
“…A previous study of 23 patients with AS demonstrated elevated levels of CPII and 846 epitope in patients with concomitant peripheral synovitis, which supports this hypothesis (23). However, increased osteoclast activation has been documented in animal models of AS (35) and bone resorption markers are increased in AS, particularly in patients with active disease (36,37).…”
Section: Discussionmentioning
confidence: 64%